2007
DOI: 10.1186/1477-7525-5-64
|View full text |Cite
|
Sign up to set email alerts
|

Recommended level of physical activity and health-related quality of life among Japanese adults

Abstract: Background: The benefits of a recommended level of physical activity on physiological health indicators such as morbidity and mortality are well-accepted, but less research has addressed whether or not the association between the recommended level of physical activity and a healthrelated quality of life (HRQOL) exists in the Japanese population. Thus, the present study examined whether the recommended physical activity would be associated with HRQOL in the general Japanese middle-aged population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
2
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 19 publications
9
53
2
16
Order By: Relevance
“…44 The direction of the association across studies showed increased level of HRQoL with higher PA among healthy, unhealthy, and elderly individuals. 45,46 The variations in the findings of our study and previous studies were due to some possible reasons. First, the previously mentioned studies used either one specific PA domain or four domains of PA as independent variables (work, transport, domestic, and leisure); however, we used two categories (active and insufficient).…”
Section: Discussioncontrasting
confidence: 44%
“…44 The direction of the association across studies showed increased level of HRQoL with higher PA among healthy, unhealthy, and elderly individuals. 45,46 The variations in the findings of our study and previous studies were due to some possible reasons. First, the previously mentioned studies used either one specific PA domain or four domains of PA as independent variables (work, transport, domestic, and leisure); however, we used two categories (active and insufficient).…”
Section: Discussioncontrasting
confidence: 44%
“…4,19,26,31,39,51 Studies have investigated the association between PA and overall QoL, and the effects of PA on specifi c domains of QoL, 4,37 and it has often been reported an association with the "physical" and "mental" domains. 19,39,41,42,46,51 Evidence supports a positive association between PA and QoL, but the state of the art is not well established. The magnitude of this association is confl icting in different populations 4,37 and inconsistent results have been found when instruments for measuring PA and QoL, as well as designs, were compared.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that regular physical activity is associated with a lower incidence of cardiovascular disease, stroke and diabetes mellitus, a reduction in risk factors of metabolic syndromes, such as hypertension, dyslipidemy and obesity, as well as mood improvement, including depression and anxiety 10 .…”
Section: Introductionmentioning
confidence: 99%